Broad Anti-Viral Capacities of Lian-Hua-Qing-Wen Capsule and Jin-Hua-Qing-Gan Granule and Rational use Against COVID-19 Based on Literature Mining - Shi, Mingfei; Peng, Bo; Li, An; Li, Ziyun; Song, Ping; Li, Jing; Xu, Ruodan; Li, Ning (Frontiers in Pharmacology, 2021)
The novel coronavirus disease 2019 (COVID-19) has become a matter of international concern as the disease is spreading exponentially. Statistics showed that infected patients in China who received combined treatment of Traditional Chinese Medicine (TCM) and modern medicine exhibited lower fatality rate and relatively better clinical outcomes. Both Lian-Hua-Qing-Wen Capsule (LHQWC) and Jin-Hua-Qing-Gan Granule (JHQGG) have been recommended by China Food and Drug Administration for the treatment of COVID-19 and have played a vital role in the prevention of a variety of viral infections. Here, we desired to analyze the broad-spectrum anti-viral capacities of LHQWC and JHQGG, and to compare their pharmacological functions for rational clinical applications. Based on literature mining, we found that both LHQWC and JHQGG were endowed with multiple antiviral activities by both targeting viral life cycle and regulating host immune responses and inflammation. In addition, from literature analyzed, JHQGG is more potent in modulating viral life cycle, whereas LHQWC exhibits better efficacies in regulating host anti-viral responses. When translating into clinical applications, oral administration of LHQWC could be more beneficial for patients with insufficient immune functions or for patients with alleviated symptoms after treatment with JHQGG.